2000
DOI: 10.1007/bf02281112
|View full text |Cite
|
Sign up to set email alerts
|

Clinical improvement in patients with orthostatic intolerance after treatment with bisoprolol and fludrocortisone

Abstract: Orthostatic intolerance is the development of disabling symptoms upon assuming an upright posture that are relieved partially by resuming the supine position. Postural tachycardia syndrome (POTS) is an orthostatic intolerance syndrome characterized by palpitations because of excessive orthostatic sinus tachycardia, lightheadedness, tremor, and near-syncope. Patients usually undergo extensive medical, cardiac, endocrine, neurologic, and psychiatric evaluation, which usually fails to identify a specific abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 27 publications
0
55
0
1
Order By: Relevance
“…Although selective beta1-adrenoreceptor blockade has been reported in literature, including our own experience [4], a more recent controlled trial (Raj SR, Circ 2009) showed that low-dose propranolol, a non-selective beta-blocker, may be more appropriate in treatment of POTS. Other recent study (Chen L, Circ J 2011) observed superiority of midodrine against selective beta1-adrenoreceptor blockers in controlling symptoms in these patients.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although selective beta1-adrenoreceptor blockade has been reported in literature, including our own experience [4], a more recent controlled trial (Raj SR, Circ 2009) showed that low-dose propranolol, a non-selective beta-blocker, may be more appropriate in treatment of POTS. Other recent study (Chen L, Circ J 2011) observed superiority of midodrine against selective beta1-adrenoreceptor blockers in controlling symptoms in these patients.…”
Section: Discussionmentioning
confidence: 92%
“…Patients' symptoms are usually palpitations, light-headedness and tremor, but syncope can also occur; non-orthostatic symptoms, such as fatigue, migraine and gastrointestinal complaints, are also common [1,3,4]. Symptoms are frequently exacerbated by heat and exercise [2].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Drug therapy of POTS includes the mineralocorticoid fludrocortisone 90 to promote intravascular volume expansion, the ␣ 1 -adrenergic agonist midodrine 87,91 to elicit peripheral vasoconstriction and reduce venous pooling, ␤-blockers including propranolol 87,92 and cardioselective agents such as bisprostol 90,93 to control the excessive sinus tachycardia, and the cholinesterase inhibitor pyridostigmine [94][95][96] to prolong the phasic effects of acetylcholine on the autonomic ganglia, leading to peripheral sympathetic vasoconstrictor output (and potentiating vagal effects) on standing (Table 3). However, adverse effects of these drugs can limit their use in patients with POTS because of the presence of comorbid symptoms.…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…2 Patients with POTS often have an exaggerated increase in plasma norepinephrine on standing. 3 This finding has driven a focus on primarily sympatholytic therapeutic strategies with central 4 or peripheral 5 targeting, or secondarily by increasing peripheral resistance 6 or by blood volume expansion. 5 There are no data addressing the alternative strategy of controlling heart rate by augmenting cardiovagal tone.…”
mentioning
confidence: 99%